Encapsulation Of Sitagliptin in Polymer-Based Microspheres for Sustained Anti-Diabetic Therapy - Singh, Priya; Singh, Sandeep Kumar; Verma, Ranjeet; Kaur, Virender; Pratap, Vijay; Dahariya, Gayatri; Bhardwaj, Anjali (Journal of Neonatal Surgery, 2025)
Sitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, is widely used for managing type 2 diabetes mellitus but suffers from a short half-life and requires frequent dosing, which may reduce patient compliance. Encapsulation of sitagliptin in polymer-based microspheres offers a promising approach for sustained anti-diabetic therapy by prolonging drug release, enhancing bioavailability, and improving therapeutic efficacy. Various biodegradable and biocompatible polymers such as albumin, chitosan, hydroxypropyl methylcellulose (HPMC), poly(lactic-co-glycolic acid) (PLGA), and Eudragit have been utilized to fabricate microspheres using techniques like spray-drying, solvent evaporation, and ionic gelation. These microspheres demonstrate favorable micromeritic properties, high drug entrapment efficiency, and controlled drug release kinetics primarily governed by diffusion mechanisms following Higuchi or Peppas models. Mucoadhesive properties of polymers like chitosan and HPMC enhance gastrointestinal residence time, resulting in better drug retention and sustained action in vivo. Studies affirm that sitagliptin-loaded microspheres achieve extended drug release ranging from 12 to 24 hours, reduce dosing frequency, and minimize side effects associated with conventional formulations. This encapsulation strategy thus represents an effective oral drug delivery system with potential to improve glycemic control, patient adherence, and overall clinical outcomes in diabetes management